Counteraction to Political Terrorism in the Russian empire on the Example of Ukrainian provinces in Late ХІХ – Early ХХ Century - S. Yu. Ivanov; R. Yu. Kazankov (Bulletin of Kharkiv National University of Internal Affairs)
The peculiarities of the fight against political terrorism in the Russian Empire on the example of Ukrainian provinces in this period have been studied. In particular, the authors have analyzed historical conditions for the formation and development of various political forces of terrorist orientation, have demonstrated the basic measures on the part of state authorities and specialized law enforcement agencies on counteracting political terrorism. The emphasis has been placed on the fact that such concepts as terror and terrorism are very often interchangeable, although there is currently no their established definition. Terrorism is an attempt to pursue political interests by violent means. Terror is usually used after revolutions in order to gain complete control over society.